BUG TRACING - Keerthika, S; Geetha, V (International Journal of Computer Sciences and Engineering, 2015)
Affording to the current setting, open foundation programs revolt is attaining motion in information system epoch. In the arena of program skill, the open foundation programs cannot be overlooked. The thinking overdue open foundation ranges towards superiority and proficiency. In Open Foundation Program growth there is a communal considerate between open foundation Programmers, correspondents and managers that professionally progresses the product quality. However superiority and adeptness of Open foundation programs be contingent upon the bug’s contemporary in the merchandise. Thus considerate and following of organization is energetic development. In Open foundation programs progress tracing of bug is most significant period. Bug Tracing scheme plays an important role in hunting of bugs. Bug succeeding system contains the large amount of substantial about the bug in open foundation programs. Signifying a good bug tracing system for any merchandise will escalation efficiency of program. So we examined the remaining bug tracing classification and find out the restrictions. Later we suggested the framework for bug tracing system based on the restrictions originated in existing bug tracing system.